A lateral flow immunoassay for the rapid identification of Candida auris from isolates or directly from surveillance enrichment broths - Chalin, Arnaud; Arvor, Antoine; Hervault, Anne-Sophie; Plaisance, Marc; Niol, Léa; Simon, Stéphanie; Volland, Hervé (Frontiers in Microbiology, 2024)
Introduction Candida auris is a recently discovered yeast with a multi-drug resistant profile associated with high mortality rates. The rapid identification of Candida auris in hospital settings is crucial to allow appropriate therapeutic and rapid implementation of infection management measures. The aim of this study was to develop a lateral flow immunoassay (LFIA) for the rapid identification of Candida auris. Methods Highly specific monoclonal antibodies were obtained by immunizing mice with membrane proteins from Candida auris which were then used to develop a LFIA whose performance was assessed by testing 12 strains of Candida auris and 37 strains of other Candida species. Isolates were grown on either Sabouraud dextrose, CHROMagarTM Candida Plus or HardyCHROMTMCandida + auris agar plates. The strains were also cultured on salt sabouraud-dextrose with chloramphenicol or a commercially available Salt-Sabouraud Dulcitol Broth with chloramphenicol and gentamicin, and processed using a simple centrifugation protocol to recover a pellet. Finally, the colonies or yeast extract were transferred to the LFIA to determine the specificity and sensitivity of the assay. Results The LFIA reached 100% specificity and sensitivity from solid agar plates. For both enrichment broths, some Candida non-auris species were able to grow, but the LFIA remained 100% specific. The use of a dextrose-based sabouraud broth resulted in earlier identification with the LFIA, with most of the Candida auris strains detected at 24 h. Conclusion The developed LFIA prototype represents a powerful tool to fight the emerging threat of Candida auris. Clinical validation represents the next step.